Health Education On The 8000 First Days Of Life Programme On The Knowledge Level Of Adolescents - Purnamawati, Tri; Relawati, Anti (Asy-Syifa : Journal of Science and Technology Nursing, 2024)
Purpose: To determine the level of knowledge of adolescent students at Fikri Junior High School about the 8000 first days of life programme. Methods: descriptive method with pre and post test design..Results: Before the health education of the 8000 HPK programme, 18 people (60%) had a poor knowledge level, 12 people (40%) had a moderate knowledge level. After health education, the value of knowledge level became good 30 people (100%). Conclusion: there is an increase in the level of knowledge of adolescents about the 8000 HPK programme using the outline map media. Education using an outcrop map is recommended as an educational learning media for teenagers.